Conservative Moments Reading Conservative Texts - Garnett, Mark (Textual Moments in the History of Political Thought, 2018)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. As a complex and multifaceted world-view, conservatism is often pigeonholed and partially understood. And while the nature of conservative ideology is warmly contested among scholars, no-one can deny its prominence in contemporary debates and its effects on the politics of everyday life. These 16 essays written by expert scholars and specialists offer a broad survey of conservative thought that extends beyond typical historical and geographic boundaries to include past thinkers like Plato and Edmund Burke, non-European conservative traditions such as Japan and Russia, and political 'practitioners' including Margaret Thatcher, Ronald Reagan and Charles de Gaulle. Each essay grapples with short primary source extracts while offering instructive criticism and commentary. Conservative Moments offers students a useful, accessible, and comprehensive exposition of this political ideology.